2016
DOI: 10.1371/journal.pgen.1006333
|View full text |Cite
|
Sign up to set email alerts
|

NUCLEAR FACTOR Y, Subunit C (NF-YC) Transcription Factors Are Positive Regulators of Photomorphogenesis in Arabidopsis thaliana

Abstract: Recent reports suggest that NF-Y transcription factors are positive regulators of skotomorphogenesis in Arabidopsis thaliana. Three NF-YC genes (NF-YC3, NF-YC4, and NF-YC9) are known to have overlapping functions in photoperiod dependent flowering and previous studies demonstrated that they interact with basic leucine zipper (bZIP) transcription factors. This included ELONGATED HYPOCOTYL 5 (HY5), which has well-demonstrated roles in photomorphogenesis. Similar to hy5 mutants, we report that nf-yc3 nf-yc4 nf-yc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 116 publications
1
43
0
1
Order By: Relevance
“…NF-Y also functions in plant photomorphogenesis, especially in hypocotyl elongation (Leyva-González et al, 2012; Mu et al, 2013; Huang et al, 2015b; Myers et al, 2016). Previous genetic evidence showed that overexpression of AtNF-YA1 and NF-YA9 changed cell identity, and led to the hypocotyl becoming greener and swollen (Mu et al, 2013).…”
Section: Main Textmentioning
confidence: 99%
See 3 more Smart Citations
“…NF-Y also functions in plant photomorphogenesis, especially in hypocotyl elongation (Leyva-González et al, 2012; Mu et al, 2013; Huang et al, 2015b; Myers et al, 2016). Previous genetic evidence showed that overexpression of AtNF-YA1 and NF-YA9 changed cell identity, and led to the hypocotyl becoming greener and swollen (Mu et al, 2013).…”
Section: Main Textmentioning
confidence: 99%
“…Previous genetic evidence showed that overexpression of AtNF-YA1 and NF-YA9 changed cell identity, and led to the hypocotyl becoming greener and swollen (Mu et al, 2013). In addition, overexpression of most NF-Y A subunits significantly reduced hypocotyl elongation (Leyva-González et al, 2012; Myers et al, 2016). However, the underlying molecular mechanism by which different A-type subunits of NF-Y regulate hypocotyl elongation requires further investigation.…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the NF-Y gene family has been identified and characterized in a number of plant species, including 23 NF-Y genes in barley (Hordeum vulgare) [12], 24 in Citrus grandis [13], 24 in peach (Prunus persica) [14], 25 in castor bean (Ricinus communis) [15], 35 in tea plant (Camellia sinensis) [16], 42 in sorghum (Sorghum bicolor) [17], 44 in banana (Musa acuminata) [18], and 51 in cassava (Manihot esculenta) [19]. Many reports have shown that NF-Y TFs are involved in various physiological and biochemical processes of plants, such as flowering [20,21], seed germination [22], hypocotyl elongation [23], photomorphogenesis [24], root development [25,26], and grain filling and endosperm development [27][28][29]. In addition, the NF-Y TFs have been found to play critical roles in responses to a variety of biotic and abiotic stresses [2,5,19], and the biological functions of some NF-Y TFs in regulating plants' responses to various abiotic stresses have been studied in detail.…”
Section: Introductionmentioning
confidence: 99%